2003
DOI: 10.1007/s00402-003-0487-y
|View full text |Cite
|
Sign up to set email alerts
|

Indomethacin versus meloxicam for prevention of heterotopic ossification after total hip arthroplasty

Abstract: Our study demonstrates that there is no statistically significant trend that indomethacin or meloxicam protects a hip arthroplasty better from heterotopic bone formation. We prefer indomethacin therapy because it is almost half the price of meloxicam therapy, and we recommend indomethacin in a 12-day treatment course given 50 mg 2 times daily as an effective, inexpensive and easily administered HO prophylaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 26 publications
0
20
0
2
Order By: Relevance
“…In recent years, more COX-2 selective inhibitors have been developed with fewer side effects (Bombardier et al 2000, Feldman and McMahon 2000, Laine 2002, Gajraj 2003) and the same pain-reducing effects (Degner et al 1998, Schoenfeld 1999, Feldman and McMahon 2000. The effect on HO of this newer class of NSAIDs is described circumstantially: the effect of meloxicam is contrasting; some studies have shown the same effect (Legenstein et al 2003, van der Heide et al 2004, while another showed inferior results (Barthel et al 2002). The effect of celecoxib has been described by Romano et al (2004), and is comparable to the effect of indomethacin.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, more COX-2 selective inhibitors have been developed with fewer side effects (Bombardier et al 2000, Feldman and McMahon 2000, Laine 2002, Gajraj 2003) and the same pain-reducing effects (Degner et al 1998, Schoenfeld 1999, Feldman and McMahon 2000. The effect on HO of this newer class of NSAIDs is described circumstantially: the effect of meloxicam is contrasting; some studies have shown the same effect (Legenstein et al 2003, van der Heide et al 2004, while another showed inferior results (Barthel et al 2002). The effect of celecoxib has been described by Romano et al (2004), and is comparable to the effect of indomethacin.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] The exact mechanism responsible for each of these pathologic new bone formations is not clear. 4,5 Various medications, e.g., aspirin, indomethacin, diclofenac, and radiation protocols with 500 rads to 1,000 rads of radiation have been tried especially after hip arthroplasty to decrease the occurrence and implications of heterotopic ossification. 6,7 These treatment modalities have side effects and complications.…”
mentioning
confidence: 99%
“…1,7,18 However, in the present study, no relationship was found between the 2 variables. Studies of total hip replacement have reported that NSAIDs may prevent HO, 8,10,17,34 but the actual effect of NSAIDs in cervical arthroplasty on HO has not been determined. In the present study, we encountered a high rate of HO, despite routinely administering NSAIDs for more than 2 weeks following surgery, which casts doubts on the idea of HO prevention using NSAIDs.…”
mentioning
confidence: 99%